A Sub‐pixel Disparity Refinement Algorithm Based on Lagrange Interpolation. Issue 4 (1st July 2017) - Men, Yubo; Zhang, Guoyin; Men, Chaoguang; Li, Xiang; Ma, Ning
Abstract : A sub‐pixel disparity refinement algorithm based on Lagrange interpolation is proposed to calculate the sub‐pixel disparity and the elevation of the target construction on the remote sensing image. The accurate integer matching feature points are obtained by improved affine scale invariant feature transform. A series of interpolation samples can be estimated through the three times magnification results of each feature matching point and its close neighbor pixels. The final sub‐pixel deviation can be calculated by the interpolation samples. Experiment results show that a more accurate elevation information can be obtained on the remote sensing image with corrective epipolar line, and an accurate sub‐pixel disparity result can be estimated without the epipolar line constraint as well.